2019
DOI: 10.1111/jcmm.14474
|View full text |Cite
|
Sign up to set email alerts
|

miR‐499 released during myocardial infarction causes endothelial injury by targeting α7‐nAchR

Abstract: The surged systemic vascular inflammation after acute myocardial infarction (AMI) aggravates the atherosclerotic endothelial injury. To explore roles of miR‐499 released from cardiomyocytes during AMI in endothelial injury. Using qPCR and ELISA, we discovered that patients with AMI had significantly increased plasma miR‐499, which was directly correlated with serum thrombomodulin, a marker for endothelial injury. Plasma of AMI patients, when incubated with human umbilical vein endothelial cells (HUVECs), signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Since miR-499 released during MI has been investigated [ 21 ], this study determined the expression levels of miR-208b, miR-122-5p, and miR-134 in the EVs isolated from the plasma of MI patients and healthy individuals. The results showed that miR-208b level in the MI-associated EVs was significantly higher than that in the normal exosomes, which indicated that miR-208b enrichment may be closely associated with the development of MI.…”
Section: Introductionmentioning
confidence: 99%
“…Since miR-499 released during MI has been investigated [ 21 ], this study determined the expression levels of miR-208b, miR-122-5p, and miR-134 in the EVs isolated from the plasma of MI patients and healthy individuals. The results showed that miR-208b level in the MI-associated EVs was significantly higher than that in the normal exosomes, which indicated that miR-208b enrichment may be closely associated with the development of MI.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal expression of miR-146a and miR-223 have also been identified in the serum of patients with sepsis; these, along with miR-122 and miR-21, have been suggested as biomarkers for the diagnosis of sepsis (29,30). A previous study also confirmed that miR-499 serves a significant role in the diagnosis of myocardial injury in sepsis (31). A number of previous studies have also focused on miR-133a, and its role in cell differentiation, skeletal muscle proliferation, cancer development and fibrosis has been confirmed (32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 83%
“…All primers used were listed in Supplementary Table S1 . The expression of target gene was normalized to GAPDH and calculated using 2 −ΔΔCt method as described previously ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot was performed following the protocol reported previously ( 18 ). Briefly, cells were lysed using RIPA lysis buffer supplemented with proteinase inhibitor cocktail (78430, Thermo Fisher Scientific, USA), sonicated and boiled for 10 min.…”
Section: Methodsmentioning
confidence: 99%